1942
DOI: 10.3181/00379727-49-13480
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hamster (Cricetus auratus) for Detection of Influenza Virus in Throat Washings.

Abstract: hypophysis of iodine deficient animals was suggested by histologicat examination of their hypophysis. These glands showed a decreased percentage of acidophils with an increased number of basophils, as is the case with thyroidectomized a n i m a f~.~~' l8 Since this hypophyseal picture in thyroidectomized animals is indicative of excessive release of thyrotropic hormone,l6+ l9, 2o it is likely that it bears the same significanw in animals lacking iodine. Goitrous thyroids would thus result from hypophyseal modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1944
1944
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the 1940s, experiments showed that hamsters inoculated with influenza viruses demonstrated no clinical signs of disease, yet they mounted a specific antibody response to the infection [ 178 ]. In the 1960s through 1980s, the hamster model was employed primarily in studies of vaccine efficacy; however, the model has been used less frequently in recent years.…”
Section: Animal Models Of Influenzamentioning
confidence: 99%
“…In the 1940s, experiments showed that hamsters inoculated with influenza viruses demonstrated no clinical signs of disease, yet they mounted a specific antibody response to the infection [ 178 ]. In the 1960s through 1980s, the hamster model was employed primarily in studies of vaccine efficacy; however, the model has been used less frequently in recent years.…”
Section: Animal Models Of Influenzamentioning
confidence: 99%
“…Previous reports from this laboratory have described the use of the hamster as an experimental model for examining the antibody response to inactivated influenza vaccines Potter, Jennings, Marine & McLaren, 1973). Earlier workers (Taylor & Parodi, 1942;Friedewald & Hook, 1948) have found that influenza viruses replicate in the lungs of hamsters and can be recovered from this tissue in high titre. These findings suggest that hamsters could provide a useful model system for the study of influenza infection and immunization.…”
Section: Introductionmentioning
confidence: 94%
“…This selected animal model needs to mimic human influenza, in terms of similarity of clinical signs, histopathologic changes and virus replication kinetics. A number of animal models such as mice [3], cotton rats [4], guinea pigs [5], hamsters [6], ferrets [7], non-human primates, such as macaques [8] have been developed, but many gaps, including clinical symptoms and transmission, remain in our understanding.…”
Section: Introductionmentioning
confidence: 99%